Tableting Turmeric Rhizome (Curcuma domestica Val.) and Mangosteen Peel (Garcinia mangostana L.) Extract as Antioxidant Supplement - Reyhani, Amalia; Sriwidodo, Sriwidodo; Chaerunisa, Anis Yohana; Umar, Abd. Kakhar; Sylvia Nurrasjid, Evi; Rahman Roestan, Mas (Universitas Padjadjaran (Unpad), 2022)
Free radicals are unstable molecules that lose electrons in their outer orbitals. These compounds can be toxins for the human body and cause various degenerative diseases. To avoid this, we need antioxidants. Examples of common sources of antioxidants are turmeric (Curcuma domestica Val.) and mangosteen rind (Garcinia mangostana L.). Both of these plants have very strong antioxidant activity but have a less favorable taste for consumption. This study aimed to obtain tablets containing turmeric rhizome and mangosteen rind extract that can cover the taste with a variety of binders. Subsequently, we observed the antioxidant activity of two extracts before and after preparation. The tableting method was wet granulation and the characterization included the physical properties of the tablets. The levels of curcumin, alpha mangosteen, and total polyphenols were also checked. The antioxidant activity was measured using the DPPH method. Based on the characterization results, NaCMC 5% was the best binder for preparing tablets containing turmeric rhizome and mangosteen rind extract with a flow rate of 11.434 g/s, repose’s angle of 29.39ᵒ, loss on drying of 2.65%, carr’s index of 15.22, hardness of 43N, friability of 0.926%, and disintegration time of 16.44 minutes. The antioxidant test result showed that the combination of turmeric extract and mangosteen rind extract with a ratio of 1:2 had the best antioxidant activity with an IC50 value of 31.01 µg/ml, alpha mangosteen level of 29.77%, and curcumin level of 27.22%. The antioxidant activity of the preparation was not changed significantly after tableting. Based on the findings, it can be concluded that the tablet formulation of turmeric rhizome and mangosteen rind extract using 5% NaCMC can be potentially used as an antioxidant supplement.